Penicillin-binding proteins and induction of AmpC beta-lactamase. - Sanders, C C (1997)
In competition assays for radiolabeled penicillin, penicillin-binding proteins (PBPs) 4, 7a, and 7b showed very high affinities for strong inducers of AmpC beta-lactamase. Loss of PBP 4 resulted in diminished inducibility. This suggests that if PBPs are involved in induction of AmpC beta-lactamase, there is probably a redundancy in function among the different PBPs.